Ser monge na Era do Vazio : um estudo do Mosteiro da Ressurreição e sua mensagem de felicidade na sociedade pós-moderna - Brandellero, Neuza de Fátima (2011)
The subject of this paper is the long monastic tradition as viewed by São Bento, known to us through the Benedictines. In this big family of Benedictines, we chose the Mosteiro da Ressurreição where they are trying to live, day by day for about thirty years, under the Rule written by São Bento in the sixth Century. Firstly, in a panoramic way, we aim to approach the monastic question until we get to the main core of the problem, that is, we want to grasp the sense of this option for a monastic hodiernal life at the Mosteiro da Ressurreição, in the context of postmodernity. In this sense, is monastic life an option to obtain fulfillment and happiness, besides bringing a contribution to society or is it only an existential escapade of the human being? We worked under the assumption that the Mosteiro has incorporated the Benedictine monastic ideal, executing it with their own peculiarities, according to the traditional monastic lines of the monastery, where the founding monks were formed and informed. Besides the bibliographical revision, this paper includes the research of primary sources, semi-oriented interviews as also participative interviews, as the work involved our participation as well as our interaction with the field of study. In accordance to this paper, it is possible to affirm that the monastic ideal is the total donation of oneself to God, through continuous prayer and work. This ideal is invested in the Mosteiro da Ressurreição, pointing to a new channel of happiness, presenting a new alternative to the hedonistic and consumerism of post-modernism. The Mosteiro da Ressurreição is the irradiating center of this new ideal. So, we could say that there is sense in opting for a monastic hodiernal life, even immersed in so many distractions as post-modern society presents to monks. Also, it is possible to say that the monks are happy people living a simple life focused on spiritual values